Prevention and treatment of oral mucositis among cancer patients in the hematology–oncology setting: a best practice implementation project. Issue 4 (18th December 2020) - Huang, Tzyy-Jen; Mu, Pei-Fan; Chen, Mei-Bih; Florczak, Kristine
ABSTRACT: Introduction: Oral mucositis refers to mucosal damage and occurs in the oral, pharyngeal, and laryngeal cavities. When patients with cancer get oral mucositis, the painful condition can cause difficulties in eating, drinking, and swallowing and may compromise the patient's nutritional status. It also may be drastically associated with infections, resulting in longer hospitalizations. Objectives: The aim of this project was to promote best practices related to oral mucositis prevention and treatment for patients in the hematology–oncology setting. Methods: This implementation project was conducted in the hematology–oncology setting at a medical center in Taiwan. The current project adopted the clinical audit methodology and integrated Lewin's Change Theory, using the JBI Practical Application of Clinical Evidence System software. Seven audit criteria that represented best practice recommendations for prevention and treatment of mucositis were used. A preimplementation audit was conducted with 30 nurses and 30 patients to measure compliance between current practice and best practice. From that audit we identified barriers and facilitators to practice change by undertaking a Getting Research into Practice analysis. A post implementation audit was conducted with 50 nurses and 50 patients at 4 months after implementing the best practice recommendations for mucositis to determine long-term compliance. Results: The seven criteria showed an improvement: nurses who received education about oral care protocols increased from 40 to 100%, patients who received education about oral care protocols increased from 23 to 98%, and patients who followed oral hygiene care protocols, including brushing of teeth, increased from 27 to 96%. There were small improvements in the following criteria: compliance with ongoing assessment of the oral cavity increased from 97 to 100%, nurses who conducted an oral pain assessment increased from 97 to 98%, and patients who followed the therapeutic oral care regimens increased from 88 to 100%. However, nurses who conducted initial assessment of the oral cavity remained at 96%. Conclusion: The implementation of best practice for enhancing prevention and treatment of oral mucositis for cancer patients in four hematology–oncology settings is possible. Lewin's Change Theory underpinned the project, which integrated blended learning strategies and communication skills which contributed to the success of this implementation project.